The Role of Nursing Interventions in Patient Satisfaction and Outcomes - Saputri, Chandra Ariani (Advances in Healthcare Research, 2023)
Purpose: This study investigates the role of nursing interventions in enhancing patient satisfaction and clinical outcomes, focusing on personalized care, interdisciplinary collaboration, technological integration, and continuous professional development. Research Design and Methodology: A mixed-methods design was employed, combining quantitative surveys and qualitative interviews. A stratified random sample of 500 patients and 100 nurses across various healthcare settings was utilized. Data collection involved structured surveys measuring patient satisfaction and health outcomes alongside semi-structured interviews exploring experiences with nursing interventions. Quantitative data were analyzed using statistical techniques, while thematic analysis was employed for the qualitative data. Findings and Discussion: The study found significant positive correlations between nursing interventions and improved patient satisfaction and outcomes. Personalized nursing care and tailored interventions led to higher patient satisfaction and improved management of chronic conditions. Interdisciplinary collaboration enhanced care quality through comprehensive and coordinated efforts supported by effective communication. Technological integration, including telehealth and electronic health records, has improved care efficiency and accessibility. Continuous professional development was crucial for maintaining high standards of care, as ongoing training had a positive impact on nurse competence and patient satisfaction. Implications: The findings underscore the importance of strategic investments in personalized care, interdisciplinary collaboration, technological infrastructure, and professional development to enhance patient outcomes. Healthcare providers and policymakers can utilize these insights to develop more effective nursing practices and policies, ultimately improving the quality of patient care. Future research should address the study's limitations by including more significant, diverse populations and exploring the long-term effects of nursing interventions.